2000
DOI: 10.1093/emboj/19.20.5418
|View full text |Cite
|
Sign up to set email alerts
|

MAPK/ERK signaling in activated T cells inhibits CD95/Fas-mediated apoptosis downstream of DISC assembly

Abstract: When T cells are activated, the expression of the CD95 ligand is elevated, with the purpose of inducing apoptosis in target cells and to later eliminate the activated T cells. We have shown previously that mitogen-activated protein kinase (MAPK or ERK) signaling suppresses CD95-mediated apoptosis in different cellular systems. In this study we examined whether MAPK signaling controls the persistence and CD95-mediated termination of an immune response in activated T cells. Our results show that activation of Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
117
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(131 citation statements)
references
References 48 publications
12
117
1
1
Order By: Relevance
“…These disparate findings may be related to the fact that these drugs, a psychostimulant vs a psychodepressant, exert opposing effects on the CNS. In fact, opiate drugs (and specifically the d-agonists) could promote survival signals in the brain through inhibition of FADD, which in turn is dependent on the activation of the antiapoptotic ERK1/2 signaling pathway (Garcia-Fuster et al, 2007), crucial for protection against Fas/FADD-mediated apoptosis (Holmstrom et al, 1999(Holmstrom et al, , 2000. Other experimental evidence has shown that cocaine alters proliferation, migration, and differentiation of human fetal brain-derived neural precursor cells (Hu et al, 2006).…”
Section: Regulation Of Fadd By Cocaine M-j García-fuster Et Almentioning
confidence: 99%
“…These disparate findings may be related to the fact that these drugs, a psychostimulant vs a psychodepressant, exert opposing effects on the CNS. In fact, opiate drugs (and specifically the d-agonists) could promote survival signals in the brain through inhibition of FADD, which in turn is dependent on the activation of the antiapoptotic ERK1/2 signaling pathway (Garcia-Fuster et al, 2007), crucial for protection against Fas/FADD-mediated apoptosis (Holmstrom et al, 1999(Holmstrom et al, , 2000. Other experimental evidence has shown that cocaine alters proliferation, migration, and differentiation of human fetal brain-derived neural precursor cells (Hu et al, 2006).…”
Section: Regulation Of Fadd By Cocaine M-j García-fuster Et Almentioning
confidence: 99%
“…Together, the results suggest that possible apoptotic signals engaged by Fas activation (see Tegeder and Geisslinger, 2004;Liao et al, 2005) would be offset by decreased signal transduction through FADD and effector caspases-8/3 (not altered by any opiate treatment). Since the activation of ERK1/2 is crucial for various antiapoptotic mechanisms (Wada and Penninger, 2004), including protection against Fas-mediated apoptosis (Holmström et al, 1999(Holmström et al, , 2000, it is tempting to conclude that opiate drugs (and specifically the d-agonists) could promote survival signals in the brain through inhibition of FADD, which in turn is dependent on the activation of ERK1/2 signaling. In this context, recent studies have shown that activation of d-opioid receptors can protect neocortical neurons from glutamate excitotoxicity (Zhang et al, 2000) and induce other cytoprotective effects (Barry and Zuo, 2005).…”
Section: Regulation Of Fadd By Opiate Drugsmentioning
confidence: 99%
“…These nonapoptotic roles for Fas/FADD are still poorly understood and may involve the activation of the ERK1/2 MAPK pathway, which is important for antiapoptotic signals (Holmström et al, 1999(Holmström et al, , 2000Wada and Penninger, 2004) and for the regulation of synaptic plasticity, learning, and memory (Kyosseva, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2 Along this line several reports indicated that TCR triggering protects from CD95-mediated apoptosis. [32][33][34] In the murine system, naïve T cells were reported to die after TCR and CD95 ligation while memory T cells were costimulated and induced to proliferate. 35 However, all systems have in common that stimulation was achieved by monoclonal antibodies instead of APC coexpressing antigen, costimulatory molecules and CD95L on the cell surface.…”
Section: Cd95l Expressed On T Cells Mediates a Dual Functionmentioning
confidence: 99%